An Australian study of telegraphists' cramp. Issue 3 (July 1971) - Ferguson, David
Abstract : Ferguson, D. (1971). Brit. J. industr. Med., 28, 280-285. An Australian study of telegraphists' cramp. An investigation of telegraphists' cramp in an Australian public service organization attempted to assess the prevalance of the disorder, the degree of its transfer from morse to keyboard operating, and possible contributory influences. From an interview of 516 telegraphists in Sydney, Melbourne, and Brisbane (93% of the available population), 73 (14%) subjects with occupational cramp and 26 (5%) with occupational myalgia were identified. The job, equipment, and work environment were also investigated. The prevalence of both disorders was much greater in Sydney than in Melbourne or Brisbane. Three-quarters (74%) of the cramp subjects had had difficulty with morse before this mode of operating was discontinued, 65% had difficulty with keyboard operating, and 50% with writing. Cramp was strongly associated with neurosis and with several other attributes. Though occupational cramp has been related to neurosis in general, to obsessive and conversion reactions in particular, to ready conditioning in neurotics, and to poor psychomotor ability in neurotics, the cause is not yet known. Work load, seating, equipment, selection, training, responsibility, and supervisory practices may each contribute in particular cases.